ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA PADA NAGARI ULAKAN KECAMATAN ULAKAN TAPAKIS - Widyanti, Rina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The study aims to find out how Accountability and Transparency of Dana Desamanagement. The analytical method used is descriptive qualitative analysis, which isanalyzing the research process using a questionnaire for Dana Desa managers andmanagers in Nagari Ulakan related to the financial reporting system implemented by theNagari Ulakan Government and then described according to Permendagri 113 in 2014.The results showed that the accountability of Dana Desa management in Nagari Ulakanformat had followed Permendagri 113 in 2014, but the reporting was not carried out ontime. Transparency of Dana Desa management in Ulakan Nagari leads to Permendagri113 in 2014, the weakness of Nagari Ulakan is that the reporting process is immediatelyreported to the Regent without going through the camat. Broadly speaking, Dana Desamanagement in Nagari Ulakan has referred to Permendagri 113 in 2014, but theimplementation has not been effective. Due to the lack of village assistants and the budgetthat is often not timely, it enters Nagari accounts. The advice that can be given is that thegovernment of Nagari Ulakan should be more effective in presenting the financialstatements of Dana Desa management in accordance with Permendagri 113 in 2014.Keywords: Accountability, Transparency, Dana Desa